Sukhoy Log gold ore deposit (Patom Highlands). Part I. Problem statement, geodynamic setting and geological structure - Vladimir V. Slokvenko; Yuri V. Kolmakov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. The uncertainty surrounding the genesis of mineralization of the Sukhoi Log giant deposit and its analogues, a question which remains unresolved. The majority of modern studies are devoted to petrology, isotope geochronology and geochemistry. However, only a paucity of published sources focuses on the study of geophysical fields of the deposit, and even these are chiefly concerned with regional-scale fields and the deep structure of the Earth's crust. The integration of detailed geophysical fields with existing studies on the formation of the Sukhoy Log mineralization will facilitate a more precise understanding of the prevailing uncertainties in this area. Aim. To analyse the structure of the geophysical and radiogeochemical fields of the deposit and to determine the likely nature of the anomalies. The first part of the work is dedicated to synthesising the most relevant geological, geophysical and geochronological information on the deposit, as well as analysing existing views on the formation of mineralisation. The reconstruction of the geodynamic development of the region, in conjunction with data on the geological and tectonic position of the deposit, contributes to a correct explanation of the causes and sequence of geophysical anomalies. Since this is a review article, its methods are searching for the most relevant and comprehensive studies on geodynamics, geochronology, petrology and metallogeny of the Sukhoi Log deposit and the Bodaibo gold bearing district; their synthesis and analysis. Results and conclusions. Gold mineralization of the Bodaibo gold bearing district was formed in difficult geodynamic conditions. There was a repeated change of geodynamic settings and tectonic regimes. The formation of the deposit occurred in several stages, which is confirmed both by geochronological studies and correlation with the geodynamic development of the region.